2022
DOI: 10.14202/vetworld.2022.65-75
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gold nanoparticles shape and dose on immunological, hematological, inflammatory, and antioxidants parameters in male rabbit

Abstract: Background and Aim: Gold nanorods (AuNRs) have gained much attention in recent years due to their promising optical and chemical properties and are hence used in applied research and industrial nanotechnology. This study was designed to investigate the effect of gold nanoparticle shape (Gold nanorods vs. gold nanosphere) on immune response in rabbit. Materials and Methods: Thirty New Zealand white rabbits were divided into six groups (n=5 rabbits). The first group is the control negative received an intraveno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 53 publications
0
1
0
Order By: Relevance
“…injection of 50 nm AuNRs did not produce any apparent toxicity in dogs. Similar results were recorded in rats [14,21], rabbits [15], and pets [16]. On the contrary, after direct exposure to naked colloidal 8 to 37 nm AuNPs, a high percentage of the mice showed loss of weight and appetite and died within 21 days [22].…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…injection of 50 nm AuNRs did not produce any apparent toxicity in dogs. Similar results were recorded in rats [14,21], rabbits [15], and pets [16]. On the contrary, after direct exposure to naked colloidal 8 to 37 nm AuNPs, a high percentage of the mice showed loss of weight and appetite and died within 21 days [22].…”
Section: Discussionsupporting
confidence: 76%
“…ROS produced by AuNPs might induce cellular damage by destructing the proteins, DNA, membranes, and other organelles like mitochondria, and nucleus [29]. In contrast, some reports have indicated that 50 nm AuNRs showed no hepatotoxicity or nephrotoxicity in rats [14,30], rabbits [15], and pets [16]. This difference might be due to the route of administration, duration of exposure, or species difference.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings indicated improved sperm quality, testosterone concentration, and nutrient digestibility in male rabbits. At the same time, similar to the NPs used, high serum antioxidant defense potential was proven in gold nanorods in the experiment by Mehanna et al (2022).…”
Section: Discussionmentioning
confidence: 65%
“…AuNP therapy reduced elevated levels of nitrite, free radicals, and sulfhydryl in the brain caused by okadaic acid [209]. Additionally, it has been observed that this therapy improves the levels of catalase, glutathione, and superoxide dismutase, which are important antioxidant enzymes involved in cellular defense mechanisms [205,209,210].…”
Section: Application Of Gold-based Nps (Aunps) and Their Antioxidant ...mentioning
confidence: 99%